2019
DOI: 10.1186/s12888-019-2353-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between post-traumatic stress disorder and suicidal ideation among shidu parents: the role of stigma and social support

Abstract: BackgroundLosing an only child is a particularly traumatic and heartbreaking event for parents, which can trigger a lot of emotional responses, including PTSD and suicidal ideation (SI). The objectives of this study were mainly to identify predictors of SI and examine the interactions of PTSD with stigma and social support on SI among shidu parents.MethodsA total of 507 shidu parents from Shenyang, China were included in this cross-sectional study. Bivariate logistic regression analyses were conducted to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
(84 reference statements)
1
17
1
Order By: Relevance
“…After losing their only child, shiduers suffer from physical and mental illnesses caused by the traumatic loss and the unique social and cultural context in China (Wang et al, 2019; Zheng & Lawson, 2015). For Chinese shiduers, the loss of an only child deprives the parents of offspring, the production of which has been regarded as a family duty (Song, Li, et al, 2018), and parents very likely feel desperate and overwhelmed about the termination of their family line.…”
Section: Pgd Symptoms After Child Deceasedmentioning
confidence: 99%
“…After losing their only child, shiduers suffer from physical and mental illnesses caused by the traumatic loss and the unique social and cultural context in China (Wang et al, 2019; Zheng & Lawson, 2015). For Chinese shiduers, the loss of an only child deprives the parents of offspring, the production of which has been regarded as a family duty (Song, Li, et al, 2018), and parents very likely feel desperate and overwhelmed about the termination of their family line.…”
Section: Pgd Symptoms After Child Deceasedmentioning
confidence: 99%
“…44 Traumatic experiences such as adverse childhood experiences (ACE) due to physical or sexual abuse, loss of a parent, or conflict at home can trigger lots of emotional responses, which can result in post-traumatic stress disorder (PTSD), depression resulting in an increased risk of suicidal behavior. 45…”
Section: Mental Disordersmentioning
confidence: 99%
“…Existing research on the influencing factors of PGD among Chinese elderly shidu parents mainly focuses on demographic characteristics. Our previous studies revealed that perceived stigma greatly exacerbated the impact of PTSD on suicidal ideation (Wang, Ren, et al, 2019) and perceived stress played a mediating role between hope and PTSD (Wang, Xu, et al, 2019). Chinese culture views the death of a child as a symbol of terrible karma and a taboo subject related to some superstitions and customs (Zheng et al, 2017).…”
Section: Introductionmentioning
confidence: 98%